ANTIOXIDANT ACTIVITY OF DRIED STRAWBERRIES JUICES (Fragaria vesca L.) EMULGEL PREPARATION USING CANDLENUT OIL AND IT’S DIFFUSION - Erwiyani, Agitya Resti (Indonesian Journal of Pharmacy, 2016)
Strawberries (Fragaria vesca L.) is a fruit that contains nutrients with many benefits and used as an antioxidant because it contains phenolic, ascorbic acid, pelargonidin-3-glucoside and cyanidin-3-glucoside. In addition, strawberries contain flavonoids, which have high antioxidant capacity. Double emulsion can improve the stability of phenolic compounds from dried strawberry juice. Primary emulsion is dispersed in a gel base (emulgel) and it is expected to produce more stable and better preparation with the ability to release the active ingredient topically. The production of double emulsion preparation (A / M / A) using candlenut oil as the oil phase with high level of total flavonoid and total anthocyanins of formula respectively - were 22.86% and 55.915%. The total flavonoid in dried strawberry juice emulgel was able to pass the membrane shed snake skin with higher flux value than the total flavonoid in the form of emulsion type A / M.